Grenada : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Modification of Quantitative Performance Criterion and Augmentation, and Financing Assurances Review; Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Third Review under the three-year arrangement for Grenada. All end-2008 quantitative targets were met. Meeting structural benchmarks on submitting investment legislation and a new Excise Bill and on completing a Country Poverty Assessment has been delayed owing to the time required to consult stakeholders, to finalize the list of excisable goods, and to complete the technical work and drafting, respectively. The performance criterion on initiating reorganization or liquidation of Capital Bank was met in November 2008.